2021
DOI: 10.1016/j.clcc.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the IDEA Collaboration Study Results on Clinical Practice in France for Patients With Stage III Colon Cancer: A National GERCOR - PRODIGE Survey

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This survey has contributed to understanding the impact of the IDEA collaboration on clinician-prescribing practices soon after first publication of the IDEA results in abstract form. Other surveys of clinicians’ opinions have been performed ( 14 , 15 ) but with fewer respondents and from different locations. The strengths of this survey are the high number of responses and the timeliness with which it was disseminated after the IDEA collaboration results were publicized, only 4 months after the initial conference presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This survey has contributed to understanding the impact of the IDEA collaboration on clinician-prescribing practices soon after first publication of the IDEA results in abstract form. Other surveys of clinicians’ opinions have been performed ( 14 , 15 ) but with fewer respondents and from different locations. The strengths of this survey are the high number of responses and the timeliness with which it was disseminated after the IDEA collaboration results were publicized, only 4 months after the initial conference presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of over 200 physicians, Ouali et al reported that 81% of participants agreed that 3 months of AC was the new standard for low-risk stage III colon cancer. 31 Similarly, Yu et al surveyed 145 international physicians, reporting that 68% agreed with the same statement. 32 Importantly, our results demonstrate that T4 and N2 staging were independent predictors of recurrence and mortality, supporting the IDEA-based risk stratification system.…”
Section: Discussionmentioning
confidence: 97%
“…In a survey of over 200 physicians, Ouali et al. reported that 81% of participants agreed that 3 months of AC was the new standard for low‐risk stage III colon cancer 31 . Similarly, Yu et al.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in patients with low-risk stage III CC, 3 months of CAPOX has become a standard of care (FOLFOX 3 or 6 months as options), whereas 6 months of FOLFOX (or CAPOX for 3 or 6 months as options) is recommended to patients with T4 and/or N2 tumors. 10-12…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in patients with low-risk stage III CC, 3 months of CAPOX has become a standard of care (FOLFOX 3 or 6 months as options), whereas 6 months of FOLFOX (or CAPOX for 3 or 6 months as options) is recommended to patients with T4 and/or N2 tumors. [10][11][12] In patients receiving 6 months of adjuvant chemotherapy, early treatment termination has been reported for about a third of patients 1,[13][14][15][16][17] with a negative prognostic impact on OS in most studies, except for one retrospective study including 616 patients treated with FOLFOX, which reported no impact on survival outcomes. 18 In current clinical practice, oxaliplatin is also often stopped early because of cumulative peripheral sensory neurotoxicity, and we have no data on the prognostic impact of early oxaliplatin discontinuation (EOD) while continuing fluoropyrimidine in patients with localized CC.…”
Section: Introductionmentioning
confidence: 99%